Design and analysis of an improved AODV protocol for black hole and flooding attack in vehicular ad-hoc network (VANET). (19th May 2019) - Kumar, Ankit; Sinha, Madhavi
Abstract: Today Vehicular Networks is not a new term. In the past three to four years, Vehicular Networking has acquired immense publicity especially in the area of Research and Academic Industry. VANET is infrastructural less network in which node connect and disconnect automatically. The basic reason behind this ever-increasing technology is that it has been one of the most valuable and recognizable research concept for enhancing efficiency and ensuring safety measures in near future transportations. VANET have node to node connectivity free mobility distribution operation, so sue to their flexible nature this network is vulnerable for many attack. In this paper we implement the attack like flooding and black hole attack using AODV routing protocol and improved AODV routing. Three different scenario are simulated using NS2.35 simulator and measure the performance parameters like end to end delay, packet overhead, packet delivery rate and packet drop ratio, which are analyzed and compared with the exiting protocol. In this simulation flooding attack routing protocol overhead is 21.8% and black hole attack routing protocol overhead is 18.04% overhead. Packet deliver ratio when flooding attack is 15.6% and in black hole attack is 10.5%, Which show that AODV routing protocol is more vulnerable than Black hole attack.